Antagonistic modulatory roles of magnesium and calcium on release of endothelium-derived relaxing factor and smooth muscle tone. - Michele E. Gold; Georgette M. Buga; K S Wood; R E Byrns; Gautam Chaudhuri; L. J. Ignarro (1990)
The objective of this study was to elucidate the mechanisms associated with the reciprocal relation between magnesium and calcium on vascular smooth muscle tone in bovine pulmonary artery and vein. Rapid removal of magnesium from Krebs-bicarbonate medium used to bathe isolated rings of precontracted artery or vein caused transient endothelium- and calcium-dependent relaxation and cyclic GMP accumulation. Both responses were antagonized by oxyhemoglobin, methylene blue, or superoxide anion and were enhanced by superoxide dismutase. The transient relaxation was followed by sustained endothelium-independent contraction. Endothelium-denuded vascular rings contracted in response to extracellular magnesium depletion without alteration in cyclic GMP levels. The data suggest that vascular endothelium-derived nitric oxide is responsible for the calcium-dependent relaxation elicited by extracellular magnesium depletion. Indeed, in bioassay cascade studies, magnesium removal from the medium used to perfuse intact artery or vein enhanced the formation and/or release of an endothelium-derived relaxing factor by calcium-dependent mechanisms. In the absence of both extracellular magnesium and calcium, calcium readdition caused transient endothelium-dependent relaxation and cyclic GMP accumulation, and both responses were abolished by oxyhemoglobin or methylene blue. In the presence of magnesium, however, readdition of calcium to calcium-depleted medium caused only contractile responses. Addition of magnesium to calcium-containing medium consistently caused endothelium- and cyclic GMP-independent relaxation that was not altered by oxyhemoglobin or methylene blue. Thus, magnesium and calcium elicit reciprocal or mutually antagonistic effects at the levels of both endothelium-derived relaxing factor formation and/or release and smooth muscle contraction. This relation may be of physiological importance, and the possibility that a reduction in circulating magnesium levels could lead to calcium-mediated vasospasm may be of pathophysiological concern.